Passive bistatic radar based on staring radar illuminators of opportunity. - Ghazalli, Nasyitah (Cranfield University, 2018)
Passive Bistatic Radar (PBR) systems use non-cooperative illuminators of opportunity to detect, localise and track targets. They have attracted considerable research interest in recent years because they can be operated and deployed at a relatively low cost, they are difficult to detect and hence allow covert operations in hostile environments, and they do not require the allocation of an increasingly more congested frequency spectrum. Various analogue and digital communication systems have been studied and exploited as illuminators of opportunity for PBR in recent years. Despite the extensive work carried out on PBR that exploit random communication signals, there has been limited research investigating the use of existing non-cooperative radar systems as illuminators of opportunity. The exploitation of radar signals to achieve passive bistatic detection is attracting as it may offer significant advantages. Because common radar waveforms are deterministic, a reference channel is essentially not required to detect a target. The knowledge of the deterministic waveform allows the passive receiver to be matched with the illuminator of opportunity and thus generate a Doppler map. Radar signals are also designed for detection and provide a large bandwidth, a good compression ratio and hence enhanced range resolution. The work presented in this thesis investigates PBR solutions that exploit nonrandom signals transmitted by non-cooperative staring radar systems. Staring radar offer a constant illumination of the volume under surveillance and, unlike radar systems that deploy a rotating antenna, offer a continuous signal of opportunity. They are very attractive illuminators in particular for short range applications to detect low-RCS and slow-moving targets, such as drones. In this research, a passive radar prototype, capable of operating with and without a reference channel, was developed and detection performance investigated on data collected in a set of experimental trials with the Thales-Aveillant Gamekeeper staring radar. Results show that moving targets, including drones, could be successfully detected with a PBR exploiting radar signals and operating with and without the reference channel.